Model Strategi Komunikasi Pariwisata Dalam Melakukan Branding Pecinan Glodok - Pinontoan, Nexen Alexandre; Djati, Sundring Pantja; Rahmanita, Myrza (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2024)
This research discusses the Tourism Communication Strategy of the DKI Jakarta Tourism and Creative Economy Department in Branding the Glodok Chinatown Area Destination as Urban Tourism. The background to this research is the great potential of the tourism communication model in branding the Glodok Chinatown area as an urban tourism destination in DKI Jakarta which highlights elements, namely historical tourism, cultural tourism and culinary tourism. The aim of this research is to analyze and evaluate the tourism communication strategies used by the DKI Jakarta Tourism and Creative Economy Department in branding the destination. The research method involves interviews, observation, and documentation analysis to collect data from various sources such as journals, websites, and books related to tourism destination branding. The research results show the success of the DKI Jakarta Tourism and Creative Economy Department in implementing various communication strategies to improve the image of Glodok Chinatown as an urban tourist destination. The implementation of cultural activities, such as festivals, art exhibitions and traditional performances, not only enriches tourism content by highlighting the region's rich culture and history, but also creates engaging experiences for tourists. The use of social media, including Instagram, YouTube, TikTok, and official websites, has become the main communication tool that has succeeded in reaching a wider audience, especially young people who are active on digital platforms. Apart from that, partnerships established with stakeholders, including tenants and local communities, are an important key in formulating and executing branding strategies, strengthening the integrity of Chinatown Glodok as a destination that involves and empowers the local community. Overall, this holistic communication strategy reflects an effective approach in introducing, introducing and developing Glodok Chinatown as an urban tourism destination, providing a strong foundation for success that can be strengthened and developed in the future.